Investigation of photosynthetic effects, carbohydrate and starch content in cress (Lepidium sativum) under the influence of blue and red spectrum - Ladan Ajdanian; Mehdi Babaei; Hossein Aroiee (Heliyon, 2020)
In order to study the effect of the quality of different LED light spectra (90%R+10%B, 60%R+40%B and control) on photosynthetic parameters (photosynthetic rate (PG), Fv/Fm and ΦPSII) of stomatal conductance, transpiration rate, carbohydrate, starch and chlorophyll index on cress (Lepidium Sativum), a pot experiment was conducted under the greenhouse cultivation-without-soil (hydroponics) condition in the form of split plot based on a completely randomized design with 6 replications. The results showed that the combined application of blue and red light spectra with different percentages had a positive and significant effect on all traits. The highest amounts of each of the photosynthetic parameters in the 60R:40B treatment were 12.4, 0.87, and 0.92 (μmol CO2 m−2 s−1), respectively, and the lowest amounts (19.6, 0.39, and 0.44 (μmol CO2 m−2 s−1)) were observed in the control treatment. The highest amounts of stomatal conductance, carbohydrate and starch of leaves which were 0.3 (cm.s−2), 5.59 and 6.44 (mg.g-1 FW), respectively, were observed in the 90R: 10B treatment as a result of red light increase. Furthermore, in the control treatment, the light source of which was the natural sunlight, the lowest amounts of 0.11 (cm.s−2), 1.98 and 1.09 (mg.g−1 FW) were observed. The highest transpiration rate (25/83 (mol.m−2.s−1)) was observed in the 60R: 40B treatment which had experienced a significant increase compared to the control light (sunlight) treatment and the lowest transpiration rate (5.5 (mol.m−2.s−1)) was in the control (sunlight) treatment. The chlorophyll index in the 60R: 40B treatment was 41.18, which showed a significant difference from the other treatments (p ≤ 0.01) and the lowest amount of 25.5 was detected in the control treatment. As a result, it can be stated that the use of blue and red light spectra in combination with different percentages can have various positive effects on the growth and development of plants; therefore, the existence of both types of spectra is suggested. This technology means that a particular combination of LED light spectra can be useful for a variety of commercial greenhouse products, especially the valuable ones.